Discussing Adolescent Sexual Health in African-American Churches - Williams, Terrinieka T. (Journal of religion and health, 2014)
This study describes the ways in which two African-American churches discuss adolescent sexual health topics. Six focus groups were conducted in two churches in Flint, Michigan, that reported no formal sexual health programming for their congregants. Three themes emerged to highlight the different perspectives about the role of churches in adolescent sexual decision-making and sexual health education: (1) churches as sources of sexual information, (2) churches as complex communities, and (3) recommendations for sexual education in churches. Participant responses suggest that churches can and should serve a resource for sexual health information. Implications for practice and research are discussed.